The Improvement Ability to Determine the Content and Mandate of Pantun through the Power Point Media of Fifth Grade Student - Deny Setyaningrum (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The problem that arises in this classroom action research is the low learning outcomes of grade 5 SD Negeri Trangkilan in determining the content and mandate of the pantun. The aim is to determine whether or not the learning outcomes have increased in determining the content and mandate of the rhymes for 5th grade students of SD Negeri Trangkilan through the use of power point media. This classroom action research with the subject of 5th grade students of SD Negeri Trangkilan in the academic year 2020/2021 with a total of 25 students. This classroom action research was conducted in 2 cycles, each cycle consisting of 4 stages, namely, planning, implementing, observing and reflecting. While the research indicator is the completeness of classical learning outcomes. The method of collecting research data is through observation and tests. From the research results indicate an increase in student learning outcomes. Based on the results of data analysis and discussion, namely as follows: that learning completeness from cycle I is 60% and cycle II is 84% means that it has increased by 24%.